Monitoring System For Academic Activity Of Muhammadiyah Vocational School In Central Java - Joni, Joni; , Bana Handaga, S.T.,M.T.,P.h.D (2017)
Muhammadiyah is an Islamic organization that has several levels of institutional networks, which one of them is Institution Center of Muhammadiyah in Central Java. It has a policy on the whole of activity in Central Java province, including in the education field. In implementing its policy education field, the institurion is still difficult to monitor outcomes academic activities of Muhammadiyah Vocational School throughout Central Java. The examples are to determine which schools should be given a scholarship, which schools need repairs, information about students, information about teachers and education personnel, information about facilities and infrastructure conditions of schools, etc. This happens because there is not computerized monitoring system of academic activities so that the development of Muhammadiyah Vocational School was less than the maximum. Therefore, in this study will be built a web-based monitoring system to monitor it. This monitoring system is built using waterfall method where the working each phase must be completed before proceeding to the next phase. The monitoring system is expected to facilitate the institution in monitoring outcomes academic activities of Muhammadiyah Vocational School. In addition, this system can facilitate the general public in the search for information related to education basic data and partial data of Muhammadiyah Vocational School throughout central java completely.